Mechanical Properties of Nickel Free High Nitrogen Austenitic Stainless Steels - LI, Hua-bing; JIANG, Zhou-hua; ZHANG, Zu-rui; XU, Bao-yu; LIU, Fu-bin (Journal of iron and steel research, international, 2007)
The nickel free Fe-Cr-Mn-Mo-N series high nitrogen austenitic stainless steels have been developed. The mechanical properties of high nitrogen austenitic stainless steels with 0.82% (A1) and 0.96% (A2) nitrogen content are investigated. The tensile deformation of A1 and A2 steels with different crosshead speed is performed at room temperature(RT), and their flow behavior is modeled. The tensile tests of A1 steel is carried out with the temperature from −196°C to 500°C. The A1 and A2 steels exhibit high strength and good ductility at RT. With increasing the crosshead speed, the tensile strength and elongation of A1 and A2 steel decrease, but their yield strength increases. The flow behavior of A1 and A2 steels is well described by the modified Ludwik equation. The flow parameters n 1 decrease with increasing the crosshead speed, which implies that the strain hardening of high nitrogen steels is more active under low crosshead speed. The strength factor K 1 true yield stress exp( K 2 ) and ɛ L increases, but the flow parameter - n 2 decreases with increasing nitrogen in the steel investigated. The ductility is improved with increasing test temperature in the range of −196°C to 300 °C. Above 300°C, the elongation of A1 steel decreases. Because transgranular cracking along {111} planes occurs, the elongation of A1 steel at −196°C decreases down to only about 5%.